Pregnancy and primary Sjögren's syndrome: management and outcomes in a multicentre retrospective study of 54 pregnancies. (2nd January 2017) - Ballester, C; Grobost, V; Roblot, P; Pourrat, O; Pierre, F; Laurichesse-Delmas, H; Gallot, D; Aubard, Y; Bezanahary, H; Fauchais, A-L
Abstract : Objectives : Primary Sjögren's syndrome (pSS) is one of the most common autoimmune diseases, mainly affecting women during the fourth decade of life. During pregnancy, the presence of anti-Ro/SSa and anti-La/SSb antibodies increases the risk of congenital heart block (CHB). Foetal and pregnancy outcomes in pregnant women with pSS compared with the general population are difficult to evaluate because of confounding factors including age and body mass index (BMI). Method : The aim of this case–control study was to analyse the impact of pSS in pregnant women on foetal and pregnancy outcomes. Results : We enrolled 19 women with pSS (54 pregnancies) matched by age and BMI to 216 controls. Patients with pSS delivered significantly earlier (38 weeks + 3 days vs. 39 weeks + 2 days) and experienced more spontaneous abortions [< 22 weeks of gestation (WG)] than the controls [n = 16/54 (30.0%) vs. n = 1/216 (0.4%); p < 0.00001]. Preterm delivery (≤ 37 +6 WG) was significantly higher in the pSS group than in the control group (29% vs. 12%, p = 0.04). pSS activity significantly affected the birthweight percentile, which was lower in pregnancies occurring after the diagnosis of pSS than in those occurring before (32.43 ± 21.57 vs. 60.46 ± 27.37; p = 0.008). No case of CHB was observed. Conclusions : pSS is responsible for an increased risk of spontaneous abortion. The duration of pregnancy is lower in patients with than without pSS, with more premature deliveries. Pregnancies that occur after the onset of the disease result in lower birthweight percentile children than when pSS is not clinically overt.